Performance of a new quantitative computed tomography index for interstitial lung disease assessment in systemic sclerosis - Bocchino, Marialuisa (Sci Rep, 2019)
Quantitative high resolution computed tomography (HRCT) may objectively assess systemic sclerosis (SSc)-interstitial lung disease (ILD) extent, using three basic densitometric measures: mean lung attenuation (MLA), skewness, and kurtosis. This prospective study aimed to develop a composite index - computerized integrated index (CII) – that accounted for MLA, skewness, and kurtosis by means of Principal Component Analysis over HRCTs of 83 consecutive SSc subjects, thus eliminating redundancies. Correlations among CII, cardiopulmonary function and immune-inflammatory biomarkers (e.g. sIL-2Rα and CCL18 serum levels) were explored. ILD was detected in 47% of patients at visual HRCT assessment. These patients had worse CII values than patients without ILD. The CII correlated with lung function at both baseline and follow-up, and with sIL-2Rα and CCL18 serum levels. The best discriminating CII value for ILD was 0.1966 (AUC = 0.77; sensitivity = 0.81 [95%CI:0.68–0.92]; specificity = 0.66 [95%CI:0.52–0.80]). Thirty-four percent of patients without visual trace of ILD had a CII lower than 0.1966, and 67% of them had a diffusing lung capacity for CO <80% of predicted. We showed that this new composite CT index for SSc-ILD assessment correlates with both lung function and immune-inflammatory parameters and could be sufficiently sensitive for capturing early lung density changes in visually ILD-free patients.